Break Point : Two Minnesota Athletes and the Road to Title IX - Brenden, Sheri, 1959- (Book collections on Project MUSE., 2022)
"Break Point tells the story of how two Minnesota teenagers took on the unequal system of high school athletics, setting a legal precedent for schools nationwide before the passage of Title IX. This scrupulously reported book is at heart the story of the girls whose pluck and determination-and heartache-led to a victory much greater than any high school championship"--